ISOLATION AND CHARACTERIZATION OF OIL DEGRADING MICROORGANISMS FROM ARZEW OIL REFINERY - DILMI, Fatiha (MEKHALDI Abdelkader, 2019)
The spills of petroleum and petroleum product, which occur during transport, storage and refining, are a major contaminant in the environment, as they produce harm to the surrounding ecosystem.Bioremediation is an efficient method used to treat petroleum hydrocarbon contaminated soil using indigenous microorganisms. The purpose of our study was to isolate, screen and identify the hydrocarbon degrading bacteria from oil polluted soil. Fifteen Oil-contaminated soil samples were aseptically collected from seven sites in Arzew oil refinery, North-West of Algeria.Physico-chemical parameters of soil samples showed that sand and loam were the predominant fractions. The soils were neutral to slightly alkaline pH, have a low salinity and highly polluted with total hydrocarbon contentranging from 2 to 86 g/kg soil. Bacterial enumerationranged from 1.6 x 105 to 1.4x 108 CFU/g soil indicating high bacterial count in oil-contaminated soilscompared with non-contaminated one. Seventy-eight bacterial colonies with different size and color were isolatedusing mineral salt media supplemented with 1% of crude oil. Twenty-two bacterial isolates were screened for their best degradative abilities of crude oil, and then they were identified based onmorphological and biochemical characterizations. Fifteen isolates were identified using 16S rRNA gene sequence analysis;the isolates were identified as the following genera and/or species:Pseudomonas aeruginosa, Achromobacter xylosoxidans, Staphylococcus haemolyticus, Enterococcus faecalis, Bacillus cereus, B.anthracis, B.subtilis, Exiguobacteriumaurantiacum,Lysinibacillusmacroides, P.fluorescens, Burkholderiacepacia, Staphylococcus hominisand Lysinibacillussphaericus.Six bacterial isolates ( identified as P. aeruginosa) showed a positive result with primer pair specific to alkane 1 monoxygenase gene (434bp). The ability of 12 isolated strains to degrade crude oil was carried out in a liquid medium by measuring optical density and gravimetric analysis. Results indicated that all the isolated strains had effectively utilized crude oilas carbon source.Pseudomonas aeruginosa (P2.1 and P2.3), LysinibacillusmacroidesB4.2and Achromobacter xylosoxidans P2.2had the highest growth in the medium with crude oil and exhibited the highest biodegradation percentage with 76.37%, 60.92%, 47.46% and 45.20% respectively. The ability of individual pure isolates and bacterial consortia to degrade diesel were determined using the turbidometry method, gravimetric analysisandGC-MS analysis. The results indicate that the bacterial consortium and Pseudomonas aeruginosaP2.1 showed the best growth in MSM with diesel and exhibited the highest biodegradation percentage of diesel with 79.62% and 64.81% respectively.The consortiumshowed the greatest effect of diesel degradation compared to individual strains.The GC-MS analysis revealed that the consortium and individual isolates degrade the aliphatic fraction greater than the aromatic fraction. All compounds in diesel were highly reduced and particularly in bacterial consortium where n-alkanes (fromC9 to C26) were almost completely degraded after 15days of incubation. The optimal culture conditions (temperature, pH, salinity, agitation speed) for the maximum biodegradation of crude oil by bacterial isolates were determined. This study indicates that the contaminated soil samples contain a diverse population of hydrocarbon degrading bacteria and these strains could be used for the bioremediation of oil-contaminated soil and other oil waste.
Keywords: Isolation, characterization, biodegradation, microorganism, crude oil, diesel, 16S rRNA, contaminated soil, ARZEW oil refinery.